1995
DOI: 10.1002/(sici)1097-4571(199505)46:4<306::aid-asi7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology in context: A database-filtering approach to identifying core and productive non-core journals supporting multidisciplinary R & D

Abstract: Eighty‐nine journals were identified as potentially important journals supporting biotechnology R&D through the analysis of journal citation networks (1991 Journal Citation Reports). Twelve research areas emerged: one set of linked intercitation clusters representing the central areas of concern—biotechnology, microbiology, molecular genetics, food science and technology, and plant science. Organic chemistry and natural products research comprised a linked pair, while the remainder, horticulture, pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It includes pharmaceutical technology [1], pharmaceutics [9], drug stability [10], and environmental toxicity [19]. It includes pharmaceutical technology [1], pharmaceutics [9], drug stability [10], and environmental toxicity [19].…”
Section: Resultsmentioning
confidence: 99%
“…It includes pharmaceutical technology [1], pharmaceutics [9], drug stability [10], and environmental toxicity [19]. It includes pharmaceutical technology [1], pharmaceutics [9], drug stability [10], and environmental toxicity [19].…”
Section: Resultsmentioning
confidence: 99%
“…CCA has been performed to explore the intellectual structure of medical informatics (Andrews 2003;Morris and McCain 1998), biomedical engineering (Garfield 1986), biotechnology (McCain 1995;Rip and Courtial 1984), genetics (McCain 1991), and so on. By conducting CCA for journals, Morris and McCain (1998) found medical informatics' major focus areas of early 1990s.…”
Section: Qualitative and Quantitative Studymentioning
confidence: 99%
“…10 McCain used a database filtering approach by combining citation, indexing, and productivity analysis to identify core and important noncore journals supporting multidisciplinary research and development in the area of biotechnology. 11 Hooper-Lane and Atkins examined the journal coverage, uniqueness versus overlap, and currency of three multidisciplinary databases in relation to marine science, and concluded that the multidisciplinary databases complemented the subject-specific databases and significantly improved recall and currency of returned results. 12 Cavanagh compared the retrieval performance of five multidisciplinary tables of contents (TOC) databases with three specialized biological databases in terms of precision and recall.…”
Section: Literature Reviewmentioning
confidence: 99%